PROBLEMS OF BUILDING A SYSTEM FOR MONITORING THE PHYSICAL CONDITION OF DIFFERENT POPULATION GROUPS (Web of Teachers: Inderscience Research, 2024)
Monitoring the physical condition of the population is necessary for the prevention and promotion of health through physical culture, and its widespread implementation requires methodological, organizational, economic and information support. The difficulty of resolving this issue is associated with a number of problems - the lack of a concept for the content and economic justification of the monitoring system; differences in the physical condition of different population groups; the emergence of new works that expand the capabilities of the survey. This paper discusses methods for monitoring the physical condition of a person and suggests options for improving the existing system.